FIFA World Cup 2006 Germany: An opportunity for union revitalisation? - Wilfried Schwetz; Donna McGuire (International Labour Organization (ILO), 2008)
Given their global dimension and centrality to late modern capitalist development mega sports events like the Olympics and the FIFA World Cup can provide space for public discussion about the impact of globalisation and the opportunity for union revitalisation. This paper examines the activities of selected German unions and civil society organisations, both in the lead up to and during the FIFA World Cup in Germany 2006, in order to determine the extent to which unions were able to utilise such opportunities for long-term strategic gains. Following an overview of the development and growth of mega sports events and the specifics of the German industrial situation, the actions of selected German unions are assessed; using union revitalisation categories as a tool, for examining the strategic processes used by these unions and to point to some areas of future potential. As this assessment shows, attempts by German unions to use the World Cup for long-term strategic gains were exceptional, rather than the general practice. In part this can be attributed to the time-frame in which the World Cup was held; the underdeveloped nature of the union revitalisation debate in Germany at the time and the specifics of the German union situation. At the same time, the power of the interest groups involved in mega sports events, the complexity of the relationships, and the level of resources needed by unions to conduct strategic campaigns and political action should not be underestimated.
Keywords: 330